Women's understandings of sexual problems: findings from an in‐depth interview study. Issue 23 (7th February 2013) - Bellamy, Gary; Gott, Merryn; Hinchliff, Sharron
Abstract : Aims and objectives: To explore women's understandings of sexual problems. Background: Prevailing knowledge about women's sexual problems has prioritised the material body. Particular attention is given to the importance of penetrative sexual intercourse, orgasm and the reproductive imperative, which fail to take account of contextual factors that contribute to women's experiences of sexual problems. Design: Qualitative in‐depth interview study. Methods: Individual in‐depth interviews conducted with 23 women aged 23–72 years, recruited from members of the general public and a psychosexual clinic. Results: The findings suggest that sexual problems are bodily experienced and socially and psychologically mediated. Women's views were influenced by the relational context of their experiences. At the same time, their views were deeply embedded within a patriarchal framework to make sense of their own sexual functioning and satisfaction. Conclusion: This study presents a challenge in the drive to medicalise women's sexual problems via the female sexual dysfunction label. It problematises the current diagnostic criteria for sexual problems outlined in the Diagnostic and Statistical Manual, which presupposes a highly individualised framework and favours a more nuanced approach. Relevance to clinical practice: Rather than adopting or eschewing an entirely medical or psychosocial model, women presenting with sexual problems should be seen by a clinician whose assessment is holistic and takes into account relational, cultural, psychosocial and health‐related concerns.